Annual Plan 2001-2002 Volume - II Government of Karnataka - Planning Commission (Planning Commission, 2001)
Scheme-wise Details of Revised Estimates in 200-01 and Outlays for Annual Plan 2001 - 02, Physical Targets and Achievements, Annual Plan (2001-02) Proposals for Spillover and Ongoing Programmes / Projects, Annual Plan (2001-02) Proposals for Maximising Benefits of Completed Programmes / Projects, Annual Plan (2001-02) Proposals for Programmes / Projects - New Schemes, Summary Statement - Annual Plan (2001-02) Proposals for Programmes / Projects, Statement regarding Externally Aided Projects, Annual Plan 2001-02 Outlays by Heads of Development - for District Plans, Centrally Sponsored Schemes, Annual Plan (2001-02) Pradhana Mantri Gramodaya Yojna (PMGY) Proposed Outlay.
Planning, Statistics and Science and Technology Department
Statistics and Science and Technology Department
Keywords: Scheme-wise Details; Revised Estimates in 200-01; Outlays for Annual Plan 2001-02; Physical Targets and Achievements; Annual Plan (2001-02) Proposals for Spillover and Ongoing Programmes/Projects; Proposals for Maximising Benefits of Completed Programmes/Projects; Summary Statement; Statement regarding Externally Aided Projects; Centrally Sponsored Schemes